Enhancing The Role Of Political Parties In Advancing Political Education As A Foundation For Democracy - Gunawan Arifin; Virgayani Virgayani; Asriyani Asriyani; Muja'hidah Muja'hidah; Jubair Jubair (Fiat Justisia: Jurnal Ilmu Hukum, 2025)
Political parties play a strategic role in democratic governance, serving as key instruments in fostering democracy. However, a decline in public trust has emerged due to the perception that political parties prioritize power politics over their educational function, reducing them to mere tools of political control. This study employs legislative, conceptual, and comparative approaches to develop a framework for strengthening the role of political parties, particularly in enhancing political education as a prerequisite for democracy. It examines two key issues: whether the current regulation of political party functions aligns with Indonesia’s democratic development model and how these functions can be reinforced to promote public political education. The findings indicate that the existing political party law has not effectively facilitated political education, failing to enhance civic awareness and responsibility in accordance with Indonesia’s democratic principles. To address this, the legal framework governing political parties must institutionalize political education and ensure that ethical and moral values serve as guiding principles in decision-making processes.